Environmentally friendly melamine composite material and preparation method thereof
By combining the modified melamine resin prepolymer with the polycarbonate polyurethane prepolymer with the synergistic effect of photoinduced composite materials, the problems of high free formaldehyde content and poor stain resistance in the melamine resin are solved, and the material has high water resistance, stain resistance, heat insulation and excellent mechanical properties are achieved.
Patent Information
- Application Number
- CN202510000132.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The existing melamine resins have problems with high free formaldehyde content and poor stain resistance, which affects their use quality.
The modified melamine resin prepolymer and polycarbonate polyurethane prepolymer are combined with photo-initiated composite materials, and the synergistic effect of the introduction of crosslinking points, alginate-L-arginine crosslinking structure and itaconic acrylate crosslinking agent is improved, and the crosslinking density and flexibility of the resin are improved through chitosan/prolandosan nanofiber-loaded riboflavin and other materials.
The free formaldehyde content in melamine resin is significantly reduced, the water resistance, stain resistance, heat insulation and mechanical properties of the material are improved, and the problems of insufficient brittleness and stain resistance of the original resin are solved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of melamine materials, and particularly relates to an environmentally friendly melamine composite material and a preparation method thereof. Background Art
[0002] Melamine resin, also known as melamine formaldehyde resin, is a high-performance synthetic resin with advantages such as corrosion resistance, water resistance, and diverse processing properties. It is used in daily necessities, machinery, electronics and other industries. In the preparation of melamine resin, the melamine resin produced has disadvantages such as poor wear resistance and toughness and high free formaldehyde content, which affects its quality in use.
[0003] For example, a Chinese patent application document with publication number CN105038120A discloses a melamine resin, which is prepared from at least the following raw materials by weight: 50-90 parts of melamine-formaldehyde resin prepolymer, 5-40 parts of plant fiber, 0.01-0.1 parts of curing agent, and 2-30 parts of inorganic rigid filler; the inorganic rigid filler is one of magnesium oxide, aluminum oxide, copper oxide, aluminum hydroxide, talcum powder, calcium carbonate, montmorillonite, barium sulfate, silicon dioxide, and titanium dioxide, or a compound of any proportion of two or more thereof. The patent application document adds inorganic fillers when preparing the melamine resin, so that the wear resistance of the melamine resin is improved. At the same time, the presence of organic matter on the surface is conducive to the dispersion of inorganic rigid particles in the matrix, so that the melamine resin has good fluidity; but the free formaldehyde content in the obtained melamine resin is relatively high.
[0004] There is free formaldehyde in the structure of melamine resin, so there is free formaldehyde in melamine resin products made of melamine resin, such as melamine resin tableware. The migration amount of formaldehyde monomer in melamine resin products often exceeds the standard. At the same time, the oil stains attached to the outer surface of melamine resin tableware and other products will make cleaning difficult. Summary of the invention
[0005] The existing melamine resin has the problems of high free formaldehyde content, poor stain resistance and the like. In order to solve the problems, the present invention provides an environmentally friendly melamine composite material and a preparation method thereof.
[0006] In order to achieve the purpose of the present invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides an environmentally friendly melamine composite material, wherein the environmentally friendly melamine composite material consists of component A and component B;
[0008] Wherein, the component A is made of the following raw materials in parts by weight: 70-80 parts of modified melamine resin prepolymer, 10-15 parts of cross-linking agent, and 2-5 parts of straw;
[0009] The component B is made of the following raw materials in parts by weight: 70-80 parts of polycarbonate polyurethane prepolymer and 15-20 parts of photoinitiated composite material;
[0010] Wherein, the preparation method of the modified melamine resin prepolymer comprises the following steps:
[0011] S1: uniformly mixing melamine and formaldehyde aqueous solution, heating for initial reaction, adjusting pH to alkaline, adding urea for secondary heating reaction, and filtering to obtain melamine urea-formaldehyde resin prepolymer;
[0012] S2: Mix alginate, L-arginine and water evenly, continuously introduce carbon dioxide gas and add CaCl 2 The aqueous solution is mixed evenly and then allowed to stand, and melamine urea-formaldehyde resin prepolymer is added and mixed evenly to obtain a modified melamine resin prepolymer.
[0013] In component A, straw has high mechanical strength and can improve the mechanical properties of the material.
[0014] Preferably, in S1, the mass ratio of melamine, formaldehyde aqueous solution and urea is 1:(2.5-5):(0.2-0.3); and the mass fraction of the formaldehyde aqueous solution is 35%-40%.
[0015] Preferably, in S1, the pH is 8-9.
[0016] Preferably, in S1, the temperature of the first heating is 70-80°C, and the time of the first reaction is 40-50 minutes; the temperature of the second heating is 85-95°C, and the time of the second reaction is 25-35 minutes.
[0017] Preferably, in S2, the mass ratio of alginate to L-arginine is (3-5):1.
[0018] Preferably, in S2, the alginate, L-arginine and water are mixed for 20-24 hours.
[0019] Preferably, in S2, the standing time is 3-5 hours.
[0020] Preferably, in S2, CaCl 2 The mass fraction of the aqueous solution is 5%-10%.
[0021] Preferably, in S2, the alginate is selected from sodium alginate and potassium alginate.
[0022] Preferably, the preparation method of the cross-linking agent comprises the following preparation steps:
[0023] Itaconic acid, vanillic acid and water are mixed evenly, and the pH is adjusted to neutral to obtain solution A; acrylic esters, initiators and solvents are added to solution A and mixed evenly, and the temperature is increased to react. After the reaction is completed, extraction, washing and drying are performed to obtain a crosslinking agent.
[0024] Preferably, the mass ratio of itaconic acid to acrylate is 1:(0.8-3); and the added amount of the initiator is 1.5%-5% of the mass of the itaconic acid.
[0025] Preferably, the mass ratio of itaconic acid to vanillic acid is 1:(0.5-1).
[0026] Preferably, the reaction temperature is 80-90° C., and the reaction time is 1-4 h.
[0027] Preferably, the acrylic acid ester is selected from one or more of 2-hydroxyethyl acrylate, methyl acrylate, hydroxypropyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate and hydroxymethyl methacrylate.
[0028] Preferably, the initiator is ammonium persulfate.
[0029] Preferably, the solvent is selected from one of propanol and isopropanol.
[0030] Preferably, the method for preparing the photoinitiated composite material comprises the following steps:
[0031] (1) mixing chitosan, pullulan and acetic acid aqueous solution uniformly, performing electrospinning, and drying to obtain chitosan / pululan nanofibers;
[0032] (2) mixing curcumin, thyme essential oil, surfactant and water evenly, adding chitosan / pululan nanofibers, mixing evenly and vacuum degassing;
[0033] (3) Add riboflavin to the system prepared in step (2) and perform ultrasonic dispersion, then add eggshell and shell and mix evenly to obtain a photoinitiated composite material.
[0034] Preferably, in step (1), the mass ratio of chitosan to pullulan is 1:(1-4).
[0035] Preferably, in step (1), the volume fraction of the acetic acid aqueous solution is 2%-5%.
[0036] Preferably, in step (1), the conditions for electrospinning are: the distance from the needle to the receiver is 10 to 15 cm, and the voltage is 10 to 15 kV.
[0037] Preferably, in step (2), the mass ratio of curcumin to thyme essential oil is 1:(1-2).
[0038] Preferably, in step (2), the amount of surfactant added is 10%-15% of the total mass of chitosan and pullulan; the surfactant is polyoxyethylene sorbitan fatty acid ester.
[0039] Preferably, in step (3), the amount of riboflavin added is 30%-50% of the total mass of chitosan and pullulan.
[0040] Preferably, in step (3), the amount of eggshell and shell added is 30%-50% of the total mass of chitosan and pullulan, wherein the mass ratio of eggshell to shell is 1:1.
[0041] Preferably, in step (3), the ultrasonic dispersion time is 20-30 min; ultrasonic dispersion is used to make riboflavin evenly adhere to the surface and interior of the nanofibers, reduce the agglomeration of riboflavin molecules, and ensure their uniform distribution.
[0042] Curcumin: Curcumin is introduced into chitosan / pululan nanofibers. Curcumin contains hydrophobic groups such as ketone groups in its molecules, which can enhance the hydrophobicity of chitosan / pululan nanofibers.
[0043] Thyme essential oil: The terpenes, alcohols and esters in thyme essential oil all have strong hydrophobic properties. When thyme essential oil is coated on the surface of nanofibers, it can form a dense hydrophobic film. In addition, thyme essential oil also has certain antibacterial and antioxidant properties, which enables the nanofibers coated with thyme essential oil to resist the attachment and growth of microorganisms and reduce the formation and accumulation of stains.
[0044] Eggshells and shells: Eggshells and shells are natural materials that are non-toxic and harmless. They also have good thermal stability and thermal insulation properties. Adding them as fillers to nanofibers can significantly improve the thermal stability and thermal insulation effects of the materials.
[0045] In a second aspect, the present invention provides a method for preparing the above-mentioned environmentally friendly melamine composite material, comprising the following steps:
[0046] (1) Adding a modified melamine resin prepolymer, a cross-linking agent and straw into a mold, mixing them evenly, and standing them to solidify to obtain a modified melamine resin embryo;
[0047] (2) The polycarbonate polyurethane prepolymer and the photoinitiated composite material are uniformly mixed, and after being impregnated with the modified melamine resin prepolymer, the prepolymer is cured under ultraviolet light to obtain an environmentally friendly melamine composite material.
[0048] Preferably, in step (1), the mixing temperature is 25-50° C. and the mixing time is 30-90 min.
[0049] Through impregnation, the modified melamine resin embryo can be better combined with the polycarbonate polyurethane prepolymer and the photoinitiated composite material to form a tighter structure and improve the overall strength and stability of the material.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] (1) The present invention prepares a modified melamine resin prepolymer, introduces urea into the melamine resin, and the amino groups in the urea react with the aldehyde groups in the free formaldehyde to generate hydroxymethylated urea derivatives, thereby reducing the free formaldehyde content in the resin and reducing the formaldehyde release amount. At the same time, the urea derivatives can react with melamine to form more cross-linking points, thereby increasing the cross-linking density of the resin. The alginate-L-arginine cross-linking structure is prepared with the assistance of calcium ions, wherein alginate can adsorb formaldehyde through its carboxyl groups, and the introduction of alginate and L-arginine can form hydrogen bonds with the amino groups in melamine to form flexible segments. These flexible segments can form internal stress buffer zones in the resin, thereby increasing the flexibility of the resin and reducing its brittleness, thereby making it less likely to break when subjected to stress.
[0052] (2) The present invention uses itaconic acid as a raw material, and performs free radical polymerization with acrylic acid esters and vanillic acid in the presence of an initiator to prepare a crosslinking agent. Active groups such as carboxyl and ester groups in the crosslinking agent react with hydroxymethyl and amino groups in the melamine resin to enhance the crosslinking density and physical properties of the resin. The hydroxyl group contained in the acrylic acid ester and the phenolic hydroxyl group in the vanillic acid can enhance the flexibility of its crosslinking network.
[0053] (3) The present invention coats a coating on the outside of the modified melamine resin embryo to increase the overall anti-fouling and hydrophobic properties; chitosan / pullulan nanofibers are loaded with riboflavin, curcumin, thyme essential oil, and eggshell and shell composite materials to improve the heat insulation and water resistance; chitosan / pullulan as a carrier can also bring a certain antibacterial effect to the whole, and the high mechanical strength of chitosan / pullulan nanofibers and the addition of eggshells and shells make the coating have higher wear resistance and can resist the wear and tear in daily use; riboflavin is used as a photoinitiator. Riboflavin may decompose under strong light, resulting in a decrease in photoinitiator efficiency. Therefore, chitosan / pullulan nanofibers are used to encapsulate riboflavin to achieve the loading of the photoinitiator riboflavin. The surface irregularity of the nanofibers can scatter light and reduce the amount of light directly incident on riboflavin. At the same time, curcumin can assist in absorbing ultraviolet rays and reduce the light intensity reaching the riboflavin molecules;
[0054] (4) The present invention prepares an environmentally friendly melamine composite material, which reduces the free formaldehyde content in the melamine resin. At the same time, the addition of degradable materials such as straw and eggshell is beneficial to environmental protection and resource conservation. The prepared environmentally friendly melamine composite material has good water resistance, stain resistance, heat insulation and other properties, and also has excellent mechanical properties. DETAILED DESCRIPTION
[0055] The technical solutions in the embodiments of the present invention are described clearly and completely below.
[0056] Pretreatment: The straw, eggshells and shells used in the following examples have been cleaned, dried and crushed.
[0057] Example 1
[0058] An environmentally friendly melamine composite material, consisting of component A and component B;
[0059] Component A is made of the following raw materials: 70 g of modified melamine resin prepolymer, 12 g of cross-linking agent, and 3 g of straw;
[0060] The component B is made of the following raw materials: 75g of polycarbonate polyurethane prepolymer, 20g of photoinitiated composite material;
[0061] Wherein, the modified melamine resin prepolymer is prepared by the following method of "preparing modified melamine resin prepolymer";
[0062] The cross-linking agent is prepared by the method of "preparing the cross-linking agent" as described below;
[0063] The photoinitiated composite material is prepared by the method of "preparing the photoinitiated composite material" described below.
[0064] The specific preparation steps of environmentally friendly melamine composite materials are as follows:
[0065] (1) Preparation of modified melamine resin prepolymer
[0066] (1a) Add 31.52 g of melamine and 126.08 g of a 35% formaldehyde aqueous solution into a three-necked flask, stir evenly, slowly raise the temperature to 70°C and react for 45 min, adjust the pH to 8 with a 30% NaOH aqueous solution, add 9.45 g of urea, continue to raise the temperature to 85°C and react for 35 min, and filter to obtain a melamine urea-formaldehyde resin prepolymer;
[0067] (1b) Add 10 g potassium alginate, 2 g L-arginine and 100 mL water into a three-necked flask and stir for 20 h. Then, continuously introduce carbon dioxide gas into the three-necked flask and add 60 mL of 5% CaCl 2The aqueous solution is stirred evenly and then allowed to stand for 3 hours, and then melamine urea-formaldehyde resin prepolymer is added and stirred evenly to obtain a modified melamine resin prepolymer;
[0068] (2) Preparation of cross-linking agent
[0069] (2a) Add 15 g of itaconic acid, 7.5 g of vanillic acid and 100 mL of water into a three-necked flask and stir evenly. Adjust the pH to 7 with a 30% NaOH aqueous solution to obtain solution A.
[0070] (2b) Add 12 g of 2-hydroxyethyl acrylate, 0.225 g of ammonium persulfate and 50 mL of propanol to solution A and stir evenly. Raise the temperature to 80 °C and react for 4 h. After the reaction is completed, a crude product is obtained. The product is extracted with dichloromethane, washed, and rotary evaporated to remove dichloromethane. The crosslinking agent is then dried in vacuo to obtain a crude product.
[0071] (3) Preparation of photoinitiator composite materials
[0072] (3a) 10 g of chitosan, 10 g of pullulan and 100 mL of 2% acetic acid aqueous solution were stirred for 45 min to obtain a mixed solution, and the mixed solution was loaded into a plastic syringe containing a metal needle. The applied voltage was fixed at 15 kV, and the distance from the tip to the receiver was 10 cm. Electrospinning was performed, and then vacuum dried to obtain chitosan / pululan nanofibers.
[0073] (3b) Add 8 g of curcumin, 8 g of thyme essential oil, 3 g of polyoxyethylene sorbitan fatty acid ester and 100 mL of water into a three-diameter flask and stir evenly, then add the chitosan / pullulan nanofibers prepared in step (3a), transfer the mixture to a homogenizer and homogenize for 3 min, and then vacuum degas for 10 min;
[0074] (3c) adding 10 g of riboflavin to the system prepared in step (3a) and performing ultrasonic dispersion for 30 min, and then adding 4 g of eggshell and 4 g of shell and stirring evenly to obtain a photoinitiated composite material;
[0075] (4) Environmentally friendly melamine composite materials
[0076] (4a) adding a modified melamine resin prepolymer, a crosslinking agent and straw into a mold, raising the temperature to 30° C. and stirring for 60 min, and standing to solidify to obtain a modified melamine resin embryo;
[0077] (4b) The polycarbonate polyurethane prepolymer and the photoinitiated composite material are uniformly stirred, and a modified melamine resin prepolymer is added for impregnation, and then cured under ultraviolet light to obtain an environmentally friendly melamine composite material.
[0078] Example 2
[0079] An environmentally friendly melamine composite material, consisting of component A and component B;
[0080] Component A is made of the following raw materials: 75g of modified melamine resin prepolymer, 10g of cross-linking agent, and 5g of straw;
[0081] The component B is made of the following raw materials: 70g of polycarbonate polyurethane prepolymer, 15g of photoinitiated composite material;
[0082] Wherein, the modified melamine resin prepolymer is prepared by the following method of "preparing modified melamine resin prepolymer";
[0083] The cross-linking agent is prepared by the method of "preparing the cross-linking agent" as described below;
[0084] The photoinitiated composite material is prepared by the method of "preparing the photoinitiated composite material" described below.
[0085] The specific preparation steps of environmentally friendly melamine composite materials are as follows:
[0086] (1) Preparation of modified melamine resin prepolymer
[0087] (1a) Add 31.52 g of melamine and 78.85 g of a 40% formaldehyde aqueous solution into a three-necked flask, stir evenly, slowly raise the temperature to 80°C and react for 50 min, adjust the pH to 9 with a 30% NaOH aqueous solution, add 7.88 g of urea, continue to raise the temperature to 95°C and react for 25 min, and filter to obtain a melamine urea-formaldehyde resin prepolymer;
[0088] (1b) Add 10 g of alginate, 3.5 g of L-arginine, and 100 mL of water into a three-necked flask and stir for 24 h. Then, continuously introduce carbon dioxide gas into the three-necked flask and add 60 mL of 10% CaCl 2 The aqueous solution is stirred evenly and then allowed to stand for 4 hours, and then melamine urea-formaldehyde resin prepolymer is added and stirred evenly to obtain a modified melamine resin prepolymer;
[0089] (2) Preparation of cross-linking agent
[0090] (2a) Add 15 g of itaconic acid, 30 g of vanillic acid and 100 mL of water into a three-necked flask and stir evenly. Adjust the pH to 7 with a 30% NaOH aqueous solution to obtain solution A.
[0091] (2b) 30 g of hydroxymethyl methacrylate, 0.75 g of ammonium persulfate and 50 mL of isopropanol were added to solution A and stirred evenly. The temperature was raised to 90° C. and reacted for 2 h. After the reaction was completed, a crude product was obtained. The product was extracted with dichloromethane, washed, and the dichloromethane was removed by rotary evaporation. The cross-linking agent was then dried under vacuum.
[0092] (3) Preparation of photoinitiator composite materials
[0093] (3a) 10 g of chitosan, 40 g of pullulan and 100 mL of 5% acetic acid aqueous solution were stirred for 50 min to obtain a mixed solution, and the mixed solution was loaded into a plastic syringe containing a metal needle. The applied voltage was fixed at 10 kV, and the distance from the tip to the receiver was 15 cm. Electrospinning was performed, and then vacuum dried to obtain chitosan / pululan nanofibers.
[0094] (3b) Add 8 g of curcumin, 12 g of thyme essential oil, 5 g of polyoxyethylene sorbitan fatty acid ester and 100 mL of water into a three-diameter flask and stir evenly, then add the chitosan / pullulan nanofibers prepared in step (3a), transfer the mixture to a homogenizer and homogenize for 3 min, and then vacuum degas for 10 min;
[0095] (3c) adding 15 g of riboflavin to the system prepared in step (3a) and performing ultrasonic dispersion for 20 min, and then adding 7.5 g of eggshell and 7.5 g of shell and stirring evenly to obtain a photoinitiated composite material;
[0096] (4) Environmentally friendly melamine composite materials
[0097] (4a) adding a modified melamine resin prepolymer, a crosslinking agent and straw into a mold, raising the temperature to 50° C. and stirring for 30 minutes, and standing to solidify to obtain a modified melamine resin embryo;
[0098] (4b) The polycarbonate polyurethane prepolymer and the photoinitiated composite material are uniformly stirred, and a modified melamine resin prepolymer is added for impregnation, and then cured under ultraviolet light to obtain an environmentally friendly melamine composite material.
[0099] Example 3
[0100] An environmentally friendly melamine composite material, consisting of component A and component B;
[0101] Component A is made of the following raw materials: 80g of modified melamine resin prepolymer, 15g of cross-linking agent, and 2g of straw;
[0102] The component B is made of the following raw materials: 80g of polycarbonate polyurethane prepolymer, 15g of photoinitiated composite material;
[0103] Wherein, the modified melamine resin prepolymer is prepared by the following method of "preparing modified melamine resin prepolymer";
[0104] The cross-linking agent is prepared by the method of "preparing the cross-linking agent" as described below;
[0105] The photoinitiated composite material is prepared by the method of "preparing the photoinitiated composite material" described below.
[0106] The specific preparation steps of environmentally friendly melamine composite materials are as follows:
[0107] (1) Preparation of modified melamine resin prepolymer
[0108] (1a) Add 31.52 g of melamine and 123.08 g of a 37% formaldehyde aqueous solution into a three-necked flask, stir evenly, slowly raise the temperature to 80°C and react for 40 min, adjust the pH to 8 with a 30% NaOH aqueous solution, add 8.45 g of urea, continue to raise the temperature to 90°C and react for 30 min, and filter to obtain a melamine urea-formaldehyde resin prepolymer;
[0109] (1b) Add 10 g of alginate, 2.5 g of L-arginine, and 100 mL of water into a three-necked flask and stir for 22 h. Then, continuously introduce carbon dioxide gas into the three-necked flask and add 60 mL of 8% CaCl 2 The aqueous solution is stirred evenly and then allowed to stand for 4 hours, and then melamine urea-formaldehyde resin prepolymer is added and stirred evenly to obtain a modified melamine resin prepolymer;
[0110] (2) Preparation of cross-linking agent
[0111] (2a) Add 15 g of itaconic acid, 12 g of vanillic acid and 100 mL of water into a three-necked flask and stir evenly. Adjust the pH to 7 with a 30% NaOH aqueous solution to obtain solution A.
[0112] (2b) Add 25 g of methyl acrylate, 0.5 g of ammonium persulfate and 50 mL of propanol to solution A and stir evenly. Raise the temperature to 85 °C and react for 3 h. After the reaction is completed, a crude product is obtained. The product is extracted with dichloromethane, washed, and rotary evaporated to remove dichloromethane. The crosslinking agent is then dried in vacuo to obtain a crude product.
[0113] (3) Preparation of photoinitiator composite materials
[0114] (3a) 10 g chitosan, 30 g pullulan and 100 mL 5% acetic acid aqueous solution were stirred for 50 min to obtain a mixed solution, and the mixed solution was loaded into a plastic syringe containing a metal needle. The applied voltage was fixed at 15 kV, and the distance from the tip to the receiver was 15 cm. Electrospinning was performed, and then vacuum dried to obtain chitosan / pululan nanofibers.
[0115] (3b) Add 8 g of curcumin, 12 g of thyme essential oil, 4.8 g of polyoxyethylene sorbitan fatty acid ester and 100 mL of water into a three-diameter flask and stir evenly, then add the chitosan / pullulan nanofibers prepared in step (3a), transfer the mixture to a homogenizer and homogenize for 3 min, and then vacuum degas for 10 min;
[0116] (3c) adding 12 g of riboflavin to the system prepared in step (3a) and performing ultrasonic dispersion for 20 min, and then adding 10 g of eggshell and 10 g of shell and stirring evenly to obtain a photoinitiated composite material;
[0117] (4) Environmentally friendly melamine composite materials
[0118] (4a) adding a modified melamine resin prepolymer, a crosslinking agent and straw into a mold, raising the temperature to 25° C. and stirring for 90 minutes, and standing to solidify to obtain a modified melamine resin embryo;
[0119] (4b) The polycarbonate polyurethane prepolymer and the photoinitiated composite material are uniformly stirred, and a modified melamine resin prepolymer is added for impregnation, and then cured under ultraviolet light to obtain an environmentally friendly melamine composite material.
[0120] Example 4
[0121] An environmentally friendly melamine composite material, consisting of component A and component B;
[0122] Component A is made of the following raw materials: 80g of modified melamine resin prepolymer, 10g of cross-linking agent, and 5g of straw;
[0123] The component B is made of the following raw materials: 70g of polycarbonate polyurethane prepolymer, 20g of photoinitiated composite material;
[0124] Wherein, the modified melamine resin prepolymer is prepared by the following method of "preparing modified melamine resin prepolymer";
[0125] The cross-linking agent is prepared by the method of "preparing the cross-linking agent" as described below;
[0126] The photoinitiated composite material is prepared by the method of "preparing the photoinitiated composite material" described below.
[0127] The specific preparation steps of environmentally friendly melamine composite materials are as follows:
[0128] (1) Preparation of modified melamine resin prepolymer
[0129] (1a) Add 31.52 g of melamine and 157.6 g of a 37% formaldehyde aqueous solution into a three-necked flask, stir evenly, slowly raise the temperature to 70°C and react for 40 min, adjust the pH to 9 with a 30% NaOH aqueous solution, add 6.31 g of urea, continue to raise the temperature to 90°C and react for 35 min, and filter to obtain a melamine urea-formaldehyde resin prepolymer;
[0130] (1b) Add 10 g of alginate, 3.5 g of L-arginine, and 100 mL of water into a three-necked flask and stir for 24 h. Then, continuously introduce carbon dioxide gas into the three-necked flask and add 60 mL of 5% CaCl 2 The aqueous solution is stirred evenly and then allowed to stand for 5 hours, and then melamine urea-formaldehyde resin prepolymer is added and stirred evenly to obtain a modified melamine resin prepolymer;
[0131] (2) Preparation of cross-linking agent
[0132] (2a) Add 15 g of itaconic acid, 15 g of vanillic acid and 100 mL of water into a three-necked flask and stir evenly. Adjust the pH to 7 with a 30% NaOH aqueous solution to obtain solution A.
[0133] (2b) Add 45 g of 2-hydroxyethyl acrylate, 0.5 g of ammonium persulfate and 50 mL of propanol to solution A and stir evenly. Raise the temperature to 90 °C and react for 4 h. After the reaction is completed, a crude product is obtained. The product is extracted with dichloromethane, washed, and rotary evaporated to remove dichloromethane. The product is then dried in vacuo to obtain a crosslinking agent.
[0134] (3) Preparation of photoinitiator composite materials
[0135] (3a) 10 g of chitosan, 10 g of pullulan and 100 mL of 2% acetic acid aqueous solution were stirred for 45 min to obtain a mixed solution, and the mixed solution was loaded into a plastic syringe containing a metal needle. The applied voltage was fixed at 10 kV, and the distance from the tip to the receiver was 10 cm. Electrospinning was performed, and then vacuum dried to obtain chitosan / pululan nanofibers.
[0136] (3b) Add 8 g of curcumin, 16 g of thyme essential oil, 3 g of polyoxyethylene sorbitan fatty acid ester and 100 mL of water into a three-diameter flask and stir evenly, then add the chitosan / pullulan nanofibers prepared in step (3a), transfer the mixture to a homogenizer and homogenize for 3 min, and then vacuum degas for 10 min;
[0137] (3c) adding 8 g of riboflavin to the system prepared in step (3a) and performing ultrasonic dispersion for 30 min, and then adding 3 g of eggshell and 3 g of shell and stirring evenly to obtain a photoinitiated composite material;
[0138] (4) Environmentally friendly melamine composite materials
[0139] (4a) adding a modified melamine resin prepolymer, a crosslinking agent and straw into a mold, raising the temperature to 40° C. and stirring for 60 minutes, and standing to solidify to obtain a modified melamine resin embryo;
[0140] (4b) The polycarbonate polyurethane prepolymer and the photoinitiated composite material are uniformly stirred, and a modified melamine resin prepolymer is added for impregnation, and then cured under ultraviolet light to obtain an environmentally friendly melamine composite material.
[0141] Comparative Example 1
[0142] Compared with Example 1, this comparative example does not carry out the preparation of step (1b) when preparing the modified melamine resin prepolymer, and the rest is the same as Example 1.
[0143] Comparative Example 2
[0144] Compared with Example 1, urea is not added when preparing the modified melamine resin prepolymer in this comparative example, and the rest is the same as Example 1.
[0145] Comparative Example 3
[0146] Compared with Example 1, no crosslinking agent is added to component A of this comparative example, and the rest is the same as Example 1.
[0147] Comparative Example 4
[0148] Compared with Example 1, this comparative example uses an equal amount of riboflavin to replace the photoinitiator composite material in component B, and the rest is the same as Example 1.
[0149] Comparative Example 5
[0150] Compared with Example 1, curcumin and thyme essential oil were not added when preparing the photoinitiator composite material in this comparative example, and the rest were the same as Example 1.
[0151] Comparative Example 6
[0152] Compared with Example 1, no eggshells and shells are added to the photoinitiator composite material of component B in this comparative example, and the rest is the same as Example 1.
[0153] Related tests
[0154] The curing time of the modified melamine resin embryos in Examples 1 to 4 and Comparative Examples 1 to 3 is shown in Table 1.
[0155] Table 1 Curing time
[0156]
[0157] By comparing Comparative Examples 1 to 3 with Example 1, it can be seen that the synergistic effect of the alginate-L-arginine cross-linking structure, urea, and the cross-linking agent can increase the cross-linking sites, promote the cross-linking and curing of the resin, and shorten the curing time; the introduction of the alginate-L-arginine cross-linking structure can form hydrogen bonds with the amino groups in melamine, weaken the electron cloud density of the nitrogen atom, reduce the reactivity of the NH bond, and easily lead to a decrease in the rate of the curing reaction and a prolonged curing time. The addition of urea and a cross-linking agent can solve this problem well.
[0158] The environmentally friendly melamine composite materials of Examples 1 to 4 and Comparative Examples 1 to 6 were subjected to migration tests using 4% (V / V) acetic acid as a food simulant in accordance with the national standard GB31604.48-2016. The test results are shown in Table 2.
[0159] Table 2 Test results
[0160]
[0161] By comparing Comparative Examples 1 to 3 with Example 1, it can be seen that the synergistic effect of the alginate-L-arginine cross-linking structure and urea can reduce the free formaldehyde content in the environmentally friendly melamine composite material.
[0162] The contact angle and impact resistance tests were performed on the environmentally friendly melamine composite materials in Examples 1 to 4 and Comparative Examples 1 to 6. The test results are shown in Table 3.
[0163] The contact angle θ of the cured coating was measured using an optical contact angle meter; the impact resistance was tested according to GB / T 1732-1993.
[0164] Table 3 Test results
[0165]
[0166] By comparing Comparative Examples 1 to Comparative Examples 6 with Example 1, it can be seen that the environmentally friendly melamine composite material prepared by the present invention has good water resistance, oil resistance and impact resistance.
[0167] The above is an exemplary description of the present invention. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or equivalent replacement that can be done by other technicians in this field without expending creative labor falls within the protection scope of the present invention.
Claims
1. An environmentally friendly melamine composite material, characterized in that: The environmentally friendly melamine composite material consists of component A and component B; Wherein, the component A is made of the following raw materials in parts by weight: 70-80 parts of modified melamine resin prepolymer, 10-15 parts of cross-linking agent, and 2-5 parts of straw; The component B is made of the following raw materials in parts by weight: 70-80 parts of polycarbonate polyurethane prepolymer and 15-20 parts of photoinitiated composite material; Wherein, the preparation method of the modified melamine resin prepolymer comprises the following steps: S1: uniformly mixing melamine and formaldehyde aqueous solution, heating to react, adjusting the pH to alkaline, adding urea to continue heating to react, and filtering to obtain melamine urea-formaldehyde resin prepolymer; S2: uniformly mixing alginate, L-arginine and water, continuously introducing carbon dioxide gas and adding CaCl2 aqueous solution, uniformly mixing and then standing, adding melamine urea-formaldehyde resin prepolymer and uniformly mixing to obtain modified melamine resin prepolymer; The preparation method of the cross-linking agent comprises the following preparation steps: Itaconic acid, vanillic acid and water are mixed evenly, and the pH is adjusted to neutral to obtain solution A; acrylic acid esters, initiators and solvents are added to solution A and mixed evenly, and the temperature is increased to react, and after the reaction is completed, extraction, washing and drying are performed to obtain a crosslinking agent; The preparation method of the photoinitiated composite material comprises the following steps: (1) mixing chitosan, pullulan and acetic acid aqueous solution uniformly, performing electrospinning, and drying to obtain chitosan / pululan nanofibers; (2) mixing curcumin, thyme essential oil, surfactant and water evenly, adding chitosan / pululan nanofibers, mixing evenly and vacuum degassing; (3) Add riboflavin to the system prepared in step (2) and perform ultrasonic dispersion, then add eggshell and shell and mix evenly to obtain a photoinitiated composite material.
2. The environmentally friendly melamine composite material according to claim 1, characterized in that: In S1, the mass ratio of melamine, formaldehyde aqueous solution and urea is 1:(2.5-5):(0.2-0.3); the mass fraction of the formaldehyde aqueous solution is 35%-40%.
3. The environmentally friendly melamine composite material according to claim 1, characterized in that: In the S2, the mass ratio of alginate to L-arginine is (3-5):
1.
4. The environmentally friendly melamine composite material according to claim 1, characterized in that: The mass ratio of itaconic acid to acrylate is 1:(0.8-3); the added amount of the initiator is 1.5%-5% of the mass of the itaconic acid.
5. The environmentally friendly melamine composite material according to claim 1, characterized in that: The acrylic acid ester is selected from one or more of 2-hydroxyethyl acrylate, methyl acrylate, hydroxypropyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate and hydroxymethyl methacrylate.
6. The environmentally friendly melamine composite material according to claim 1, characterized in that: In the step (1), the mass ratio of chitosan to pullulan is 1:(1-4).
7. The environmentally friendly melamine composite material according to claim 1, characterized in that: The added amount of riboflavin is 30%-50% of the total mass of chitosan and pullulan.
8. A method for preparing the environmentally friendly melamine composite material according to any one of claims 1 to 7, characterized in that: The steps include: (1) Adding a modified melamine resin prepolymer, a cross-linking agent and straw into a mold, mixing them evenly, and standing them to solidify to obtain a modified melamine resin embryo; (2) The polycarbonate polyurethane prepolymer and the photoinitiated composite material are uniformly mixed, and after being impregnated with the modified melamine resin prepolymer, the prepolymer is cured under ultraviolet light to obtain an environmentally friendly melamine composite material.
Citation Information
Patent Citations
Melamine resin
CN105038120A
Melamine resin based on recycled renewable resources as well as preparation method and application thereof
CN112724595A
Modified melamine formaldehyde resin and melamine coating liquid and preparation method thereof
CN117683194A